2020
DOI: 10.1093/gerona/glaa100
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip Strength Asymmetry and Weakness Together Are Associated With Functional Disability in Aging Americans

Abstract: Background Evaluating handgrip strength (HGS) asymmetry may help to improve the prognostic value of HGS. This study sought to determine the associations of HGS asymmetry and weakness on future activities of daily living (ADL) disability in a national sample of aging Americans. Methods The analytic sample included 18,468 Americans aged ≥50 years from the 2006–2016 waves of the Health and Retirement Study. A handgrip dynamomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 31 publications
11
58
0
Order By: Relevance
“…Performing this simple test may help physicians assess both the mental health and physical status of elderly patients. The findings of this study are consistent with previous studies reporting that HGS asymmetry and weakness together are jointly associated with adverse health conditions in older populations [ 19 21 ]. Our results suggest that HGS asymmetry has potential as a new indicator of HGS in the elderly, although subsequent studies are needed to confirm its usefulness in clinical settings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Performing this simple test may help physicians assess both the mental health and physical status of elderly patients. The findings of this study are consistent with previous studies reporting that HGS asymmetry and weakness together are jointly associated with adverse health conditions in older populations [ 19 21 ]. Our results suggest that HGS asymmetry has potential as a new indicator of HGS in the elderly, although subsequent studies are needed to confirm its usefulness in clinical settings.…”
Section: Discussionsupporting
confidence: 93%
“…McGrath et al [ 19 ] found that HGS asymmetry was associated with functional limitations in older Americans in their cross-sectional study. Therefore, asymmetric HGS may represent an asymmetry in motor function, which leads to physical imbalance and functional limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporating other aspects of muscle function in HGS protocols such as digit grip strength, submaximal force control, fatigability, neuromuscular steadiness, and asymmetry will expand how muscle function is assessed, while also maintaining procedural ease and scalability. For example, HGS asymmetry and low maximal HGS together were associated with greater odds for functional disability than each measure alone [ 13 ], and HGS asymmetry is linked to early all-cause mortality [ 14 ]. As such, evaluating other aspects of muscle function outside of maximal strength may uncover deficits in muscle function that are not otherwise identified by maximal HGS.…”
Section: Introductionmentioning
confidence: 99%